Effect of feeding frequency on growth performance, nutrient digestibility, diarrhea incidence and blood profiles in weaning pigs - KANG, HYOKON; KANG, SEONGIL; NA, YOUNGJUN; KWON, HYOUNCHUL; LEE, SANGRAK (The Indian Journal of Animal Sciences, 2019)
An experiment was conducted to evaluate the effect of feeding frequency on growth performance, nutrient digestibility, diarrhea incidence and blood profiles in weaning pigs. Piglets (264) (Average BW, 7.6 kg), were allotted to 2 treatments with 6 replicated pens (22 animals per pen; 11 males and 11 females) in a randomized complete block design based on body weight. Equal amount of diet was provided to all the animals. They were fed an early weaning diet for 14 d and a late weaning diet for 14 d. The control group was fed the diet twice (at 0700 and 1900 h) per day and treatment group was fed the diet four times (at 0700, 1100, 1500 and 1900 h) per day. The change of feeding frequency did not affect feed intake, body weight gain and gain to feed ratio. With increase in the feeding frequency, blood cortisol concentration was not changed. Also, in leptin and ghrelin analysis, there was no significant difference between treatments. Likewise, dry matter digestibility and diarrhea incidence showed no significant difference. In conclusion, the change of feeding frequency in weaning pigs did not affect the growth performance, nutrient digestibility, diarrhea incidence and blood profiles.